Supplemental Instruction Volume 2: Student Learning Processes - Strømmen-Bakhtiar, Abbas; Helde, Roger; Suzen, Elisabeth (Waxmann Verlag, 2021)
Supplemental Instruction is a program designed to support students in their learning process. The program consists of advanced students supervising new students, where the purpose is to improve students' performance and reduce the risk of interruption of studies. Supplemental Instruction was established almost 50 years ago and is used today in universities around the world. This book is about student learning processes and Supplemental Instruction, which includes everything from learning activities in SI to developing guidance skills of leaders and more. The book also deals with a comparison of Supplemental Instruction with other group-oriented learning activities, and practical aspects of the programme. The book is aimed at anyone who is concerned about study quality in higher education. The contributors are researchers and lecturers at various universities from several countries. The book is part of a trilogy on Supplemental Instruction, where the themes for the other books are "Digital Technologies" and "Organisation and Leadership". The editors of the trilogy are Abbas Strømmen-Bakhtiar (Professor), Roger Helde (Associate Professor) and Elisabeth Suzen (Associate Professor), all three at Nord University, Norway.